2011
DOI: 10.3390/ijms12042750
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Hexane Extract and Decussatin from Stembark Extract of Ficus congensis

Abstract: Ficus congensis (Moraceae) is used traditionally in the treatment of various diseases including infectious diseases, infertility, and gastrointestinal disorders. Investigation of hexane extract of the stem bark using chromatographic techniques led to isolation of a xanthone, 1-hydroxy-3,7,8-trimethoxyxanthone (Decussatin). The compound was elucidated based on spectroscopic methods such as nuclear magnetic resonance (NMR), UV, IR, and mass spectrometry (MS). Decussatin and the hexane extract were screened in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…The MIC values of the dichloromethane extract are not shown in Figure 1, since the extract was not active against any of the bacterial strains. The hexane extract of the bark of A. mearnsii showed potent antibacterial activity against E. coli with MIC value of 10.0 mg/ml and the results were almost similar to those of hexane extracts of the bark of Ficus congensis reported by Alaribe et al (2011) with MIC values of 8.0 mg/ml.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The MIC values of the dichloromethane extract are not shown in Figure 1, since the extract was not active against any of the bacterial strains. The hexane extract of the bark of A. mearnsii showed potent antibacterial activity against E. coli with MIC value of 10.0 mg/ml and the results were almost similar to those of hexane extracts of the bark of Ficus congensis reported by Alaribe et al (2011) with MIC values of 8.0 mg/ml.…”
Section: Resultssupporting
confidence: 78%
“…According to Alaribe et al (2011) the same bacterial species was not inhibited by the extract. In this study, the hexane extract showed activity against four Grampositive bacterial strains with MIC value of 10.0 mg/ml but was not active against S. faecalis.…”
Section: Resultsmentioning
confidence: 93%
“…The need for new classes of safe and natural antimicrobials able to control the microorganism growth and infections has become more urgent [1]. Synthetic drugs have been associated with several side effects on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the antimicrobial activity of chemical constituents of the oils, alone or in combination, in different treatments using different microorganisms can produce lethal effects at lower doses, avoiding changes and providing various perspectives on the problem of bacterial resistance to antibiotics [1, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids A-D were yellow needle-like crystals with the following molecular weights: A, 302 g/mol; B, 302 g/mol; C, 288 g/mol and D, 288 g/mol. The four flavonoids were extracted and synthesized at the Inner Mongolia Medical University (Hohhot, China) (15), and uniformly mixed into the basic feeds of the experimental rats. Anti-FAS (MHCD9528) was purchased from Thermo Fisher Scientific, Inc. (Carlsbad, CA, USA), and anti-phospho AMPK (AA393), anti-AMPK (AA393-1; Beyotime Institute of Biotechnology, Shanghai, China), and horseradish peroxidase-conjugated anti-mouse (NCAM-1/CD56; R&D Systems, Inc., Minneapolis, MN, USA) and anti-rabbit (ab191866) antibodies were purchased from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%